Chronic hypometabolism in striatum and hippocampal network after traumatic brain injury and their relation with memory impairment – [18F]-FDG-PET and MRI 4 months after fluid percussion injury in rat - Yasmin, Amna; Jokivarsi, Kimmo; Poutiainen, Pekka; Pitkänen, Asla; Gröhn, Olli; Immonen, Riikka (Brain research, 2022)
[Display omitted] •Striatum has metabolic deficits in chronic stage after lateral fluid percussion injury.•[18F]-FDG-PET shows low glucose uptake across hippocampal network.•Striatal hypometabolism identifies rats with severe memory impairment.•MRI: Atrophy or cerebral blood flow do not correlate with glucose uptake. Hippocampal and thalamo-cortico-striatal networks are critical for memory function as well as execution of a variety of learning strategies. In subjects with memory impairment as a sequel of traumatic brain injury (TBI), the contribution of late metabolic depression across these networks to memory deficit is poorly understood. We used [18F]-FDG-PET to measure chronic post-TBI glucose uptake in the striatum and connected brain areas (septal and temporal hippocampus, thalamus, entorhinal cortex, frontoparietal cortex and amygdala) in rats with lateral fluid-percussion injury (LFPI). Then we assessed a link between network hypometabolism and memory impairment. At 4 months post TBI, glucose uptake was decreased in ipsilateral striatum (10%, p = 0.027), frontoparietal cortex (17%, p = 0.00009), and hippocampus (22%, p = 0.027) as compared to sham operated controls. Thalamic uptake was 6% lower ipsilaterally than contralaterally, p = 0.00004). At 5 months, Morris water maze (MWM) showed memory impairment in 83% of the rats with TBI. The lower the hippocampal or striatal [18F]-FDG uptake, the poorer the MWM performance (hippocampus: r = −0.471, p < 0.05; striatum: r = −0.696, p < 0.001). Striatal [18F]-FDG-PET identified the injured animals with memory impairment with 100% specificity and sensitivity (AUC = 1.000, p = 0.009). Interestingly, the low striatal glucose uptake was a better diagnostic biomarker for memory impairment than the reduced hippocampal (AUC = 0.806, p = 0.112) or entorhinal (AUC = 0.528, p = 0.885) glucose uptake. The volumetric atrophy assessed in T2 weighted MRI or the gliotic area in Nissl staining did not correlate with glucose uptake. Arterial spin labeling did not indicate any reduction in the striatal blood flow. Our study suggests that TBI-induced chronic hypometabolism in striatum contributes to the cognitive deficits.